Proceedings of the 2nd International Workshop on Systems Development in SOA Environments 2008
DOI: 10.1145/1370916.1370924
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation for enterprise SOA APIs

Abstract: SAP recently began offering access to web services through its Enterprise Service-Oriented Architecture (E-SOA) platform. It is in the best interest of SAP that its E-SOA service operations are easier for developers to use and understand, which will contribute to higher E-SOA adoption, and a more effective means of innovation on the part of business customers. To facilitate such a change, Carnegie Mellon University's Human-Computer Interaction Institute is working with SAP's E-SOA and Business Process Renovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
17
0
2
Order By: Relevance
“…An (old) overview of the project is [1]. There are many papers about the Whyline [2,3], the study of hard-to-answer questions [4,5], the visualization tool to help with reverse engineering [6], some studies of APIs [7][8][9][10], and tools to help with APIs [11][12][13][14][15].…”
Section: For More Informationmentioning
confidence: 99%
“…An (old) overview of the project is [1]. There are many papers about the Whyline [2,3], the study of hard-to-answer questions [4,5], the visualization tool to help with reverse engineering [6], some studies of APIs [7][8][9][10], and tools to help with APIs [11][12][13][14][15].…”
Section: For More Informationmentioning
confidence: 99%
“…In a similar way, Heer et al [9] analyzed the usability of their prefuse toolkit. An interesting alteration of this approach was proposed by Beaton et al [2]. Participants first have to write in pseudo code what they would expect in the API for a certain task and then perform the real task using the API.…”
Section: Challenges For the Evaluation Of An Apimentioning
confidence: 99%
“…Our previous research has shown that programming using eSOA APIs is not simple if APIs are providing access to powerful business functionality [1,2]. Some barriers we identified included long names for services, different behaviors of services due to different business behavior, parameters of the services as hierarchies of objects with complex dependencies driven by internal, not exposed, business logic, and lack of example code [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Some barriers we identified included long names for services, different behaviors of services due to different business behavior, parameters of the services as hierarchies of objects with complex dependencies driven by internal, not exposed, business logic, and lack of example code [1,2]. The current paper presents the results of a new user study of the usability of the online documentation provided by SAP for their SOA product.…”
Section: Introductionmentioning
confidence: 99%